Water for All? An Empirical Study of Operational Efficiency in the Jal Jeevan Mission - Das, Dr. Bijay (The Eastasouth Management and Business, 2025)
One of the most important things for living is water. A reliable supply of drinkable water is essential to the advancement of humanity. In the year 2019, Jal Jeevan Mission (JJM) was introduced by the Government of India under the Ministry of Jal Shakti with an objective of providing 55 liters of water per person per day to every rural household through Functional Home Tap Connections (FHTC) by the year 2024. The present study basically tries to light up the JJM program in India through the SWOT analysis and present status of the JJM program in India. The study is completely based on secondary sources of data. The results of the study shows that the financial year 2020-21 has the highest number of households have tap water connections and the financial year 2023-24 has the highest amount of funds drawn under this JJM scheme.